Целіакія у хворих на цукровий діабет 1-го типу - Зуєв, К. О.; Губська, О. Ю.; Когут, Д. Г.; Гирявенко, О. Я.; Підаєв, А. В.; Якушевська, С. Я. (Clinical Endocrinology and Endocrine Surgery, 2012)
Celiac disease – disorder genetically caused alimentary gluten intolerance is the most frequent concomitant pathology of type 1 diabetes. It depends of common moments of both autoimmune diseases pathogenesis. Clinical manifestations of celiac disease are various and exhibit autoimmune lesions of different organs and increased cancer risk. Timely diagnosed celiac disease and assigned gluten-free diet led to significant decrease of frequency of clinical manifestations of disease. Modern clinical guidelines for the management of diabetes recommend screening of celiac disease among patients with type 1 diabetes as it has high clinical significance.